Pengaruh Parameter Proses 3D Printing Terhadap Kuat Bentur Menggunakan Fiamen Polycarbonate - Rivaldi, Muhammad; Yunus, Muhammad; Pristiansyah, Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The existence of this 3D printing technology in manufacturing has brought big companies to the world of industry. One of the rapid prototyping technologies that are often found in the market today is the FDM type of technology. Fused Deposition Modeling (FDM) technology is a printing technique used to print products using fibrous materials, printed products have ideal geometric characteristics. Impact test is a method used to determine the strength, hardness and ductility of a material. In this impact test, rapid loading is used. The method used is Taguchi and this study aims to obtain optimal process parameters in the impact test. Printing was carried out with a 3D printing machine Creality Ender 3 which printed 81 specimens. Then the impact test was carried out so that the highest average value of the impact test results was in experiment number 27 with a value of 0.00392 joules and for the lowest impact test value was in experiment number 1 with a value of 0.00291 Joules. The method used in this process parameter optimization research is the Taguchi L9 OA method. for the factors used, namely printing speed, infill layer thickness, wall thickness, print temperature. . the results of the research that has been carried out show the optimum parameter values ​​and parameters that influence the impact test successively, namely printing speed (40mm/s), infill layer thickness (0.2mm), wall thickness (2.0mm), print temperature (250 ℃), bed temperature(250℃), infill overlap(30mm), raft extra margin(7.5mm), wall printing speed(22.5mm/s). It was found that the highest average value of the impact test results was in experiment number 2 with a value of 0.031 joules and the lowest impact test value was in experiment number 7 with a value of 0.026 Joules.